Pathogenic mechanisms of autoantibodies: circulating and local antibodies that form immune complexes - Andrade, Luís Eduardo Coelho (Henry Stewart Talks, 2020)
Autoantibodies as important elements in the definition of the autoimmunity concept, Basis for the association of autoantibodies and autoimmune diseases, Autoantibodies that exert direct pathogenic effects and damage target tissues, Autoantibodies targeting extracellular antigens